„Samotny idę po mizernym stepie”. Wokół poezji Jana Huskowskiego - Prabucki, Krzysztof (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The aim of the article is to present Jan Huskowski, outline his biography and to generally identify his literary strategy. This outline is a reconnaissance, focusing on the motifs and characteristic elements of Huskowski’s poems, typical of his creative imagination. The subject of study is the poetry book Po drodze (Along the way), published in Lviv in 1907, which is a collection of poetry published mostly in the Lviv press.